2022
DOI: 10.29303/jaa.v7i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Corporate Social Responsibility Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Dan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Pertambangan

Abstract: The firm's value is important for the company because it affects its survival in the future. Many factors can affect firm value, such as disclosure and management of the capital structure. Disclosure is made to provide information to the public about the company, one of which is the disclosure of Corporate Social Responsibility (CSR) as a form of responsibility in terms of economic, environmental and social aspects. Capital structure management is carried out to achieve a balance between liabilities and equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 4 publications
1
6
0
1
Order By: Relevance
“…Based on the results of the study, it shows that the Debt to Equity Ratio affects the Company Value in Property, Real Estate, and Building Construction companies. this is supported by research conducted by Rasyid et al (2022) andM. Sari et al (2020) and does not support the research of Assa et al (2021).…”
Section: The Effect Of Der On Firm Valuementioning
confidence: 87%
See 1 more Smart Citation
“…Based on the results of the study, it shows that the Debt to Equity Ratio affects the Company Value in Property, Real Estate, and Building Construction companies. this is supported by research conducted by Rasyid et al (2022) andM. Sari et al (2020) and does not support the research of Assa et al (2021).…”
Section: The Effect Of Der On Firm Valuementioning
confidence: 87%
“…This ratio can be sought by comparing all debt with all equity. On research Rasyid et al (2022) found that DER has an influence on Corporate Value as well as on research M. Sari et al (2020) obtaining that DER also affects Company Value.…”
Section: H3: Tax Avoidance Affects Firm Valuementioning
confidence: 95%
“…This study agrees with earlier studies. Due to the high investment costs associated with reporting CSR, which lowers the operational performance value of the company, Nur (2021) and Rasyid et al (2022) concluded that there is no correlation between CSR disclosure and company value in Indonesian mining companies.…”
Section: Simple Linear Regression Testmentioning
confidence: 99%
“…Journal of Management and Bussines (JOMB) 5 ( 2) 1344-1359 kecil, bisnis biasanya membutuhkan lebih banyak dana. Saham baru dapat diterbitkan atau hutang dapat dinaikkan untuk meningkatkan modal tambahan (Rasyid et al, 2022). Kuantitas aset yang dimiliki perusahaan, jumlah pendapatan yang dihasilkannya, dan daya jualnya semuanya dapat digunakan untuk menghitung ukuran perusahaan.…”
Section: Ukuran Perusahaanunclassified